van Gogh’s Tight Shoes: Derrida Unshoeing Heidegger and Shapiro: Тесните чевли на ван Гог: Дерида ги разобува Хајдегер и Шапиро - Džeparoski, Ivan; Bužarovska, Rumena (Identities: Journal for Politics, Gender and Culture, 2004)
Author(s): Ivan Džeparoski | Иван Џепароски Title (English): van Gogh’s Tight Shoes: Derrida Unshoeing Heidegger and Shapiro Title (Macedonian): Тесните чевли на ван Гог: Дерида ги разобува Хајдегер и Шапиро Translated by (Macedonian to English): Rumena Bužarovska | Румена Бужаровска Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 3, No. 2 (Winter 2004) Publisher: Research Center in Gender Studies - Skopje and Euro-Balkan Institute Page Range: 133-154 Page Count: 11 Citation (English): Ivan Džeparoski, “van Gogh’s Tight Shoes: Derrida Unshoeing Heidegger and Shapiro,” translated from the Macedonian by Rumena Bužarovska, Identities: Journal for Politics, Gender and Culture, Vol. 3, No. 2 (Winter 2004): 133-154. Citation (Macedonian): Иван Џепароски, „Тесните чевли на ван Гог: Дерида ги разобува Хајдегер и Шапиро“, Идентитети: списание за политика, род и култура, т. 3, бр. 2 (зима 2004): 133-154.